Outros canteiros: possibilidades e limites da produção de moradias por autogestão de Belo Horizonte - Giselle Oliveira Mascarenhas (2022)
This thesis deals with the production of autogestion housing in Belo Horizonte (BH) in two moments: the first generation marked by the insurgency of the 'sem-casa' movement in the city and the construction of a municipal housing program; and the second generation made possible by the creation of a national program, the Programa Crédito Solidário (PCS). Seeking to check the possibilities and limits of the intricate and contradictory productive arrangements involved in the experiences resulting from the so-called 'institutionalized autogestion', it starts with a historical characterization of the general picture of the conventional production of housing for the poor in the country divided between 'production of interest social hegemonic' and 'marginal(ized) autogestion'. To highlight the importance of the process of historical awareness of the possibilities of 'other construction sites', the hypothesis is verified that the autogestionary experiences carried out in BH have been subjected to a process of invisibility and a consequent erasure. In order to denounce and combat the historical invisibility that entangles and reduces the powers of these and other experiences that contradict the hegemonic interests of capital, the research that subsidizes the thesis is dedicated to building a method of gathering information - which combines documentary research, historicaland field — capable of recording the memories and the current state of this production. From two case studies, the narratives of the main groups of agents involved in the investigated production are contemplated. In the recovery of the phases of organization, design, construction and post-occupancy, the case study of the Villarégia complex, supported by the stories of the Urucuia and Fernão Dias complexes, represents the first generation; while the study undertaken in the Mar Vermelho I complex, punctuated by references to the Santa Rosa II complex, summarizes the production of the second generation. Evidencing the agents; the relations and forces of production; as well as the socio-spatial developments, the thesis recalls through different voices the productive arrangement of autogestion in BH.